2015
DOI: 10.4172/2167-0269.1000175
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Preference for the Various Teaching Methods in Tourism Courses: A Case of Tourism Management Department, Madawalabu University

Abstract: This study was design to assess the student's preference of the various teaching methods in tourism management department, Madawalabu University. Students and teacher were the subjects of the study. Lottery randomization sampling technique was employed to select 23 s from 1 st , 2 nd and 3 rd year student for the questionnaires. Five teachers were purposively selected for in-depth interviews including the team leader. Six formal lesson observations were conducted. Qualitative data was narrated and presented th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…However, it is important to recognise cultural differences and it has been found that some hospitality students in China reject active learning method due to a fear of misunderstanding and a change from the more traditional teacher-oriented approach (Aynalem et al 2015). However, Penfold and Pang (2008) claimed that email was sent to all students on the 4th of February 2020.…”
Section: Application Of Teaching Styles In Hospitality Educationmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it is important to recognise cultural differences and it has been found that some hospitality students in China reject active learning method due to a fear of misunderstanding and a change from the more traditional teacher-oriented approach (Aynalem et al 2015). However, Penfold and Pang (2008) claimed that email was sent to all students on the 4th of February 2020.…”
Section: Application Of Teaching Styles In Hospitality Educationmentioning
confidence: 99%
“…The results demonstrated that the idea of abandoning lectures seemed unreasonable, as with class sizes increasing and resources becoming scarce, the lecture (with discussion) method offers a means to present content material to large numbers of students and, therefore, is efficient as a teaching method. Aynalem et al (2015) identified students' teaching preference in the tourism field, where a blended method of lecturing and in-class activities was discussed and acknowledged as the most positive. Furthermore, lecture/discussion and case study/team project were identified as the most prominent mixture.…”
Section: Prefer Learning Content Prior To Class and Use The Class Tim...mentioning
confidence: 99%
See 1 more Smart Citation